Mulla Sadra's Metaphysics and Its Influence on Indonesian Islamic Thought - Muslim, Selamet Saiful (TAJDID, 2020)
This article aims to elaborate on the metaphysical concepts of Mulla Sadra, one of the greatest Muslim thinkers and philosophers in the 16th century. This study also tries to find common ground and the influence of Mulla Sadra's philosophy on Indonesian Islamic Thought. This study uses the literature analysis method. In which, the author not only reads the relevant literature, but also evaluates in depth and critically about previous research literatures on Mulla Sadra's philosophy. The results showed that Mulla Sadra's philosophy wanted to achieve an understanding of life from the perspective of spirituality or spiritualism which was conveyed rationally while still based on Islamic Shari'a. Mulla Sadra's philosophy has a strong influence on the flow of Islamic thought in Indonesia